Identification of preschoolers with special educational needs: comparing the discriminative validity of the Strengths and Difficulties Questionnaires (SDQ) and the Achenbach System of Empirically Based Assessment (ASEBA) across different informants in Hong Kong - Wong, Terry Tin-Yau; Tang, Jacqueline Wai-Yan; Choi, Pokky Poi-Ki; Leung, Terence Siu-Chung (Frontiers in Psychology, 2025)
BackgroundEarly behavioral and emotional problems are associated with poor developmental outcomes. It is thus important to identify preschoolers with behavioral and emotional problems so that effective interventions can be provided for them early. The current study aimed to compare the screening efficiency of the parent and teacher versions of the Strengths and Difficulties Questionnaire (SDQ) and the Achenbach System of Empirically Based Assessment (ASEBA) in identifying children with early behavioral and emotional problems.MethodA community sample (n = 312) aged 3 to 5, as well as a clinical sample (n = 79) of the same age, were recruited. Parents and teachers of these participants completed the relevant forms of SDQ as well as the Child Behavior Checklist for Ages 1.5–5 (CBCL/1½-5)/Caregiver-Teacher Report Form (C-TRF).ResultsBoth instruments yielded satisfactory internal consistency and test–retest reliabilities. Teachers’ reports were more accurate in terms of differentiating the clinical sample from the community sample, and the SDQ-T yielded more consistent discriminative validity across different ages.DiscussionPsychologists, psychiatrists and allied healthcare professionals are recommended to use teachers’ report, or the SDQ-T in particular, to identify preschoolers who may require further assessment for their behavioral and emotional issues.